2019
DOI: 10.1186/s12863-019-0738-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of HSP90 gene family in Nicotiana tabacum

Abstract: BackgroundHeat shock proteins 90 (HSP90s) are a highly conserved protein family of cellular chaperones widely found in plants; they play a fundamental role in response to biotic and abiotic stresses. The genome-wide analysis of HSP90 gene family has been completed for some species; however, it has been rarely reported for the tobacco HSP90 genes.ResultsIn this study, we systematically conducted genome-wide identification and expression analysis of the tobacco HSP90 gene family, including gene structures, evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 65 publications
6
17
0
Order By: Relevance
“…The HSP90AAs are highly heat inducible, whereas HSP90ABs are constitutively expressed in Arabidopsis and rice (Yabe et al, 1994;Swindell et al, 2007;Hu et al, 2009). Similar heat response patterns of HSP90s within a subfamily are observed in Populus and allotetraploid tobacco (Zhang et al, 2013;Song et al, 2019). Meanwhile, previous studies also demonstrate the conservation in terms of exon-intron structures and protein motifs of HSP90s within a subfamily during plant evolution (Chen et al, 2006;Xu et al, 2012;Zhang et al, 2017).…”
Section: Introductionsupporting
confidence: 54%
“…The HSP90AAs are highly heat inducible, whereas HSP90ABs are constitutively expressed in Arabidopsis and rice (Yabe et al, 1994;Swindell et al, 2007;Hu et al, 2009). Similar heat response patterns of HSP90s within a subfamily are observed in Populus and allotetraploid tobacco (Zhang et al, 2013;Song et al, 2019). Meanwhile, previous studies also demonstrate the conservation in terms of exon-intron structures and protein motifs of HSP90s within a subfamily during plant evolution (Chen et al, 2006;Xu et al, 2012;Zhang et al, 2017).…”
Section: Introductionsupporting
confidence: 54%
“…As least twice as many LIM genes have been identified in vertebrates than in invertebrates and fungi, which means that the gene expansion of the LIM family mainly occurs in the late stage of species evolution. This is similar to many other gene families that contain many members, such as bHLH, HSP90 and GAP [25,36–38]. Generally, there was no significant variation in the physicochemical characteristics (pI & MW) between the 30 organisms from different lineages studied herein.…”
Section: Discussionsupporting
confidence: 78%
“…Arabidopsis HSP90.1 and HSP90.3 have furthermore been shown to be differentially expressed during different developmental processes . In contrast, detailed expression studies of the 21 Nicotiana tabacum HSP90 isoforms revealed, that HSP90 isoforms phylogenetically clustering with Arabidopsis HSP90.1 are highly stress inducible . In other respects, most studies have not included all four cytoplasmic isoforms in their experimental setups limiting our current understanding on their functional divergence.…”
Section: Hsp90 Isoforms In the Model Plant Arabidopsismentioning
confidence: 99%